Women’s Labor Force Participation in the Kurdistan Region of Iraq : A Study of Social and Psychological Barriers - Iman, Sen (World Bank, Washington, DC, 2022)
Women’s labor force participation in the Kurdistan Region of Iraq is very low, at 14 percent. This paper investigates a number of social and psychological barriers to participation, using recent methods in the measurement of social norms and cultural beliefs and primary data collected from all three governorates. Furthermore, since greater growth in employment generation is expected in the private sector, the paper explores women and men’s perceptions toward working in the private sector in detail. The findings show that while 70 percent of women and men support women’s participation in the private sector, several challenges remain in both information about the sector, as well as perceived risks and discrimination. More broadly, the findings show that traditional gender role expectations may still impede women’s labor force participation. Perceptions of common societal practices and beliefs of other members from the same household are all correlated with women’s work. The paper explores additional mental barriers using a smaller sample of younger and more educated female job seekers, who are registered with a jobs agency, and finds that both perseverance in the job search process and trust and engagement with formal institutions are additional behavioral barriers.